2015
DOI: 10.1002/ejlt.201400382
|View full text |Cite
|
Sign up to set email alerts
|

Rosemary plant (Rosmarinus officinalis L.), solvent extract and essential oil can be used to extend the usage life of hazelnut oil during deep frying

Abstract: In this study, the effects of rosemary (Rosmarinus officinalis L.) plant (RP), its alcoholic extracts (REE and RME) and essential oil (REO) on the oxidative stability of hazelnut oil (HO) during deep frying were investigated. HOs containing rosemary additives had lower conjugated diene (CD) content, p-anisidine value (AV) and polar material content compared to control values. Additionally, changes in L*, a*, and b* color values and viscosity were lower than control values. RP (50 g/kg) caused the highest reten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 40 publications
0
8
1
Order By: Relevance
“…Fatty acid composition of the hazelnut oil was in agreement with those of previous studies (Alasalvar et al, ; Alasalvar, Shahidi, Ohshima, et al, ; Karabulut et al, ), while the concentrations of the total tocopherols were found to be lower as compared to those of the reported values (Alasalvar et al, ; Karabulut et al, ). The induction period of hazelnut oil at 150 °C (27.37 min) was higher than the value reported in our previous study (25.98 min) (Tohma & Turan, ).…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…Fatty acid composition of the hazelnut oil was in agreement with those of previous studies (Alasalvar et al, ; Alasalvar, Shahidi, Ohshima, et al, ; Karabulut et al, ), while the concentrations of the total tocopherols were found to be lower as compared to those of the reported values (Alasalvar et al, ; Karabulut et al, ). The induction period of hazelnut oil at 150 °C (27.37 min) was higher than the value reported in our previous study (25.98 min) (Tohma & Turan, ).…”
Section: Resultscontrasting
confidence: 77%
“…Induction periods of oxidized hazelnut oil samples were determined according to our previous study (Tohma & Turan, ) at 150 °C using the DSC instrument (Shimadzu DSC 60, Tokyo, Japan). For this purpose, 2.0 ± 0.1 mg of oil was weighed into aluminum DSC pan and placed into oven without cover and another pan without sample was kept as reference.…”
Section: Methodsmentioning
confidence: 99%
“…After all, during the frying process, a remarkable part of the frying medium, vegetable oils, is taken up by the fried products to the extent that the sensory properties of the vegetable oils are able to strongly influence the sensory properties of the fried products (Taha et al, 2014;Tohma & Turan, 2015). There is no doubt that the consumer will refuse to use the vegetable oils if the fried products are not attractive to them.…”
Section: Influences Of Antioxidants On Sensory Properties Of Chinesmentioning
confidence: 99%
“…where volatile compounds present as gingerols, shogaols, paradoxes and zingerone have antioxidant activity by elimination of free radicals. To conclude, add that the use of rosemary (Rosmarinus officinalis L.) and sage (Salvia officinalis L.) extracts are already formally accepted in the European regulations as a new food additive and assigned with its number E-392 (Tohma & Turan, 2015).…”
Section: Results (Optional)mentioning
confidence: 99%